2014
DOI: 10.1016/j.pscychresns.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary examination of cortical neurotransmitter levels associated with heavy drinking in posttraumatic stress disorder

Abstract: Posttraumatic stress disorder (PTSD) patients have low cortical concentrations of γ-aminobutyric acid (GABA) and elevated glutamate (Glu) as measured by proton magnetic resonance spectroscopy (1H MRS). Alcohol use disorder (AUD) is highly comorbid with PTSD, but the neurobiological underpinnings are largely unknown. We wanted to determine if PTSD patients with AUD have normalized cortical GABA and Glu levels in addition to metabolite alterations common to AUD. We compared brain metabolite concentrations in 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 50 publications
2
51
1
1
Order By: Relevance
“…Higher glutamate in the parieto-occipital cortex has been linked to insomnia symptoms in patients with post-traumatic stress disorder [30,31] but has not been linked to PI per se [32,33,34]. …”
Section: Spectroscopy Neuroimaging Studies Of Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…Higher glutamate in the parieto-occipital cortex has been linked to insomnia symptoms in patients with post-traumatic stress disorder [30,31] but has not been linked to PI per se [32,33,34]. …”
Section: Spectroscopy Neuroimaging Studies Of Insomniamentioning
confidence: 99%
“…Conversely, positive allosteric modulators of the GABA A receptor (e.g., benzodiazepines, “z drugs”, and barbiturates) have sedating effects and are efficacious short-term treatments for insomnia [41,42]. With one exception that found that individuals with PI had higher GABA concentrations than GS in the occipital cortex [32], the majority of 1H MRS studies suggest insomnia is associated with lower GABA levels in the parieto-occipital cortex [30,31,33,34] or anterior cingulate [33]. Because MRS reflects presynaptic concentrations of GABA, these findings may suggest that insomnia involves impaired inhibitory control.…”
Section: Spectroscopy Neuroimaging Studies Of Insomniamentioning
confidence: 99%
“…Perturbations in the glutamatergic system have also been replicated in human population. In a recent magnetic resonance spectroscopy (MRS) study, patients with PTSD compared with trauma-exposed controls were shown to have elevated glutamate levels in the lateral temporal cortex and lower levels in ACC in PTSD with alcohol use disorder (Pennington, Abe, Batki, & Meyerhoff, 2014). Elevated serum glutamate levels were recently reported in patients with PTSD 3 months after a traumatic accident compared with healthy controls (Nishi et al, 2015).…”
Section: Glutamatergic Systemmentioning
confidence: 99%
“…However, many studies posit that co-regulation of excitation and inhibition may be important for network stability and that excitation:inhibition (E:I) imbalance may be a factor in some psychiatric conditions (Dorrn et al, 2010; Gouty-Colomer et al, 2015; House et al, 2011; Katagiri et al, 2007; Vogels et al, 2011). Notably, decreased GABA levels as well as GABA receptor binding and polymorphisms have been associated with PTSD (Bremner et al, 2000; Feusner et al, 2001; Geuze et al, 2008; Meyerhoff et al, 2014; Pennington et al, 2014; Rossi et al, 2009; Rosso et al, 2014), and reduced GABA levels are predictive of disease progression (Vaiva et al, 2006; Vaiva et al, 2004). Changes in inhibitory synaptic markers suggest that plasticity of GABAergic transmission in the basolateral amygdala may also be a feature of aversive memory formation under normal conditions (Chhatwal et al, 2005; Heldt and Ressler, 2007; Lin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%